?Atypical Work? and Compensation - John T. Addison; Christopher J. Surfield (Institute for the Study of Labor (IZA), 2005)
Atypical work, or alternative work arrangements in U.S. parlance, has long been criticized for providing poorly-compensated employment. Although one group of atypical workers (contractors) seems to enjoy a wage premium, our cross-section results from the CPS and NLSY for the better-known category of temporary workers point to a negative wage differential of some 7-12 percent. It emerges that much of the latter disparity stems from unobserved worker heterogeneity (accounting for which supports a wage advantage for contracting work). Turning to fringes, the appearance in cross section of a potentially large deficit in atypical worker health benefits is again reduced after accounting for permanent unobserved individual heterogeneity. But on this occasion the reduction is very modest. Further, there is now some indication that the wage advantage of contract workers partly compensates for their reduced access to such benefits.
Keywords: J31; J4; J33; 330; atypical/contingent work; alternative work arrangements; wage differentials; employer-related health insurance; Ungeschützte Beschäftigung; Lohnstruktur; Krankenversicherung; Betriebliche Sozialleistungen; Schätzung; Vereinigte Staaten